Methods for semantic analysis of the state of the process of functioning of a system for detecting, preventing and eliminating the consequences of computer attacks - V. O. Shablya; S. A. Konovalenko; E. O. Orlov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The aim of the study is to determine the most effective method of semantic analysis of the state of the process of detection, prevention and elimination of consequences of computer attacks. Method. The study was conducted based on the methods of semantic analysis of the state of the process of SOPKA operation. Result. A structural model of the system of semantic analysis of the state of the process of SOPKA operation is proposed, which is capable of providing an analysis of the state of the process of detection, prevention and elimination of consequences of computer attacks. The most effective method for solving the problem of semantic analysis of the state of the process of SOPKA operation is machine learning using ontological modeling. Conclusion. The results indicate the need for further research of the system of semantic analysis of the state of the process of detection, prevention and elimination of consequences of computer attacks.